Simulação numérica do efeito da prensagem em canais equiangulares (ECAP) na homogeneidade de deformação de titânio comercialmente puro - Costa, Vagner dos Anjos (2023)
Pressing in equiangular channels (ECAP) is a process of severe plastic deformation of materials, which seeks to produce the refinement of granulometry in the microstructure. Materials subjected to ECAP processing show improvements in their mechanical properties, such as the association between increased mechanical strength and increased ductility. The process variables that interfere in the microstructural refining are: matrix types, processing route and number of deformation passes. The present work has the objective of virtually evaluating the levels of deformation by eight passes via ECAP of titanium in a commercially pure state, in a matrix with a channel angle of 120º and confronting an experimental study with the intention of comparing the levels of deformation between regions of the test body. The specimen and the matrix were numerically modeled and simulated by finite elements using the modeling interface and the Abaqus simulation environment – student edition 2020. In the deformation simulation, the ECAP matrix was registered using parameters of a rigid body material, that is, it was not subject to deformation throughout the process, given that the interest was to analyze the deformations in the studied material. The virtually deformed material was commercially pure titanium, the physical parameters were previously established through the registration of physical and mechanical variables in the Abaqus environment. The material was submitted to eight deformation passes in the ECAP matrix, in a processing route A, and the results were analyzed to verify the total deformations that the material was submitted. Using computer simulation software, the behavior of the material was determined as a function of the variables involved in the process, with subsequent experimental comparison. In this way, it is possible to previously analyze its subsequent physical application with greater reliability, greater knowledge of the material to be worked on the test specimens, greater economy with the anticipation of problems that precede the real experimental practice, thus avoiding errors and obtaining greater accuracy in its treatment.